Strategic Interactions In The Malaysian Automotive Industry : Emperical And Game Theoretical Analysis - You, Carolyn Lian See (2003)
The AFTA imminent in 2005 has been alerting all concerns in the Malaysian automotive industry. The intensity of competition particularly concerns the industry where there is a gradual decline in national makes’ performance, but an increased in the non-national makes especially in the passenger car segment. This paper derives the game theoretical model of firms conducts and applies it to the industry level to examine the strategic interactions in the elements of structure – conduct – performance paradigm (SCP) with Malaysian Government’s intervention. The Herfindah Index (HHI) indicates the decreased in market concentration, hence increase competition in the industry. This leads to increase in advertising intensity but has no impact on barriers to entry. The results also reveal no drastic changes in new vehicles’ pricing and national cars should lead in product launches to regain market share.